Four new Bent-toed geckos (Cyrtodactylus Gray: Squamata: Gekkonidae) from northeast India - Purkayastha, Jayaditya; Lalremsanga, Hmar Tlawmte; Bohra, Sanath Chandra; Biakzuala, Lal; Decemson, H.t.; Muansanga, Lal; Vabeiryureilai, Mathipi; Chauhan, Suraj; Rathee, Yashpal Singh (Zootaxa, 2021)
Based on morphology and ND2 gene sequences, four new species of Cyrtodactylus, two each from the Indian states of Meghalaya and Mizoram are described herein. The new species are a part of the Cyrtodactylus khasiensis group. The species from Meghalaya represent the lowland clade whereas the species from Mizoram represent the highland clade within the south of Brahmaputra clade of Indo-Burmese Cyrtodactylus. The two distinct populations from Meghalaya are sister to one another, differing from each by an uncorrected p-distance 0.065 and collectively are sister to Cyrtodactylus septentrionalis. The species from Mizoram differ from each other by an uncorrected p-distance of 0.085–0.121 and collectively are sister to Cyrtodactylus montanus.